Modern Trends in the Organization of Scientific Activities in the Field of Physical Culture Education (Eurasian Journal of Learning and Academic Teaching, 2022)
The article identifies and substantiates a scientific systematic approach to studying the effectiveness of student learning management in higher education physical education classes. The concept of "Management of student learning in physical education classes in higher education" is explained. The system of principles of management of students' educational activity in physical education classes of higher education is theoretically based. According to the practical nature of the research, the theoretical content and conclusions are placed at the level of the specific technology of student learning management in physical education classes